Air Trapping and the Risk of COPD Exacerbation: Analysis From Prospective KOCOSS Cohort - Kim, Youlim; Kim, Sang Hyuk; Rhee, Chin Kook; Lee, Jae Seung; Lee, Chang Youl; Kim, Deog Kyeom; Shin, Kyeong-Cheol; Jung, Ki Suck; Yoo, Kwang Ha; Park, Yong Bum (Frontiers in Medicine, 2022)
Background and Aims Air trapping is a predictive index for a decline in lung function and mortality in patients with chronic obstructive pulmonary disease (COPD). However, the role of air trapping in COPD exacerbation has rarely been studied. Therefore, this study aimed to investigate the impact of air trapping as a continuous parameter on COPD exacerbation. Materials and Methods To evaluate air trapping, we identified the ratio of residual volume (RV) to total lung capacity (TLC) of patients with COPD from the Korean COPD Subgroup Study (KOCOSS) cohort, which is a multicenter-based, prospective, consecutive cohort in Korea. The primary outcome was a development of COPD exacerbation during 3 years of follow-up. Results Of 2,181 participants, 902 patients measured the RV/TLC ratio in the baseline enrollment, and 410 were evaluated for assessing the development of COPD exacerbation. Of 410 patients, the rate of moderate to severe exacerbation and severe exacerbation was 70.7% and 25.9%. A 10% increase of RV/TLC ratio increased the risk of the moderate to severe exacerbation by 35% and severe exacerbation by 36%. In subgroup analysis, an interaction effect between triple inhaled therapy and the RV/TLC ratio for severe exacerbation nullified the association between the RV/TLC ratio and severe exacerbation (p for interaction = 0.002). Conclusions In this prospective cohort study, we found that air trapping (representing RV/TLC ratio as a continuous parameter) showed an association with an increased risk of COPD exacerbation, particularly in patients who have not undergone triple inhaler therapy.